Isolation and Characterization of Carbapenem-Resistant Escherichia coli Carrying blaNDM and mcr-1 from Recurrent Urinary Tract Infection Patient - Liang Chen; Jiyong Jian; Zeqiang Xie; Ping Zhao; Man Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. The emergence of carbapenem-resistant E. coli (CRECO), leading to few antibacterial drugs available for CRECO infection. In this study, we report three carbapenem-resistant Escherichia coli (E. coli) isolates coproducing blaNDM and mcr-1 from patients with recurrent urinary tract infection (RUTI). Carbapenem-resistant E. coli strains, E55, E84, and E85, were isolated from the urine sample of RUTI patients. Methods. Antimicrobial susceptibility testing (AST) was conducted with VITEK-2 compact system and Kirby–Bauer (K-B) disk diffusion method. The ESBL test was detected by the disk diffusion method. The EDTA-modified carbapenem inactivation method (eCIM) and modified carbapenem inactivation method (mCIM) were performed for screening the carbapenemase. Multilocus sequence typing (MLST) was performed for molecular typing of the strains. The resistance genes were detected by PCR. Results. The three isolates were all susceptible to tigecycline and nitrofurantoin. The blaNDM-1, blaCMY-6, blaTEM-1 and blaCTX-M-1, mcr-1, and porin loss expression of outer membrane protein F (OmpF) were detected in E55, which was assigned to ST2. The E84 and E85 were identified as ST471 carrying blaNDM-5, blaCTX-M55, and blaTEM-1 and the quinsolone-resistant genes aac(6′)-Ib-cr and mcr-1. Conclusion. To our knowledge, our study is the first to report carbapenem-resistant E. coli strains carrying blaNDM and mcr-1 from urine of the recurrent urinary tract infection patients. These E. coli strains carrying blaNDM and mcr-1 should be closely monitored.